Avståndsbestämning till AGB-stjärnor genom parallaxmätning - Andersson, Karl; Johansson, Benjamin; Ovik, Otto; Wetterberg, Philip (My University, 2026)
In this thesis distance to nearby AGB-stars – stars in the end of their lifecycle with a mass of 0.8–8.0M⊙ – were calculated using parallax. The characteristical dynamic of these stars creates intensity fluctuations which together with their giant size makes measuring the coordinates of the stars a non trivial task. Different methods for estimating the centre point of the stars were evaluated. To obtain a good resolution of the stars that were examined – R Doradus, R Leonis, W Hydrae, Mira A and B – several observations, separated in time, from the ALMA-telescope were used. Estimates for the parallax and proper motion – the stars apparent movement on the celestial sphere, excluding parallax – were extracted by fitting the stars celestial movement for the different methods. To achieve a better precision the resampling method jackknife were used. The methods that gave the best result were gaussian fit and different variants of half max intensity fit. The gaussian fit gave the distances: 47 +4 −3 pc for R Doradus, 134 +71 −35 pc for R Leonis, 106 +29 −19 pc for W Hydrae, 121 +34 −23 pc for Mira A and 126 +55 −31 pc for Mira B. The calculated astrometric values agrees with values from the space telescopes Hipparcos and Gaia, however, the calculated values for the proper motion have a better precision in comparison. Further studies of the binary star Mira should take its orbit into account.
Keywords: AGB-stars, parallax, proper motion, ALMA, R Dor, R Leo, W Hya, Mira